(untitled) (Bangladesh Journal of Endosurgery, 2014)
Objective: To evaluate the outcome of extracorporeal shock wave lithotripsy (ESWL) for the management of upper ureteral stones. Materials and methods: This prospective observational study assessed 42 patients who underwent ESWL from March 1, 2009 to June 30, 2010 in the National Institute of Kidney Diseases and Urology, Dhaka. The stone size, success rate, and postoperative complications were evaluated. A successful outcome was defined as the patient being stone-free on radiography 1 month after treatment. Results: Out of 42 patients, 34 had stone size more than 1 cm and the remaining had stone size less than 1 cm. Stone clearance rate after single session was 36 (85.7%). Immediate complications included fever in 14 and severe hematuria in 6 patients. Almost 50% developed urinary tract infection, and steinstrasse was observed in 2 patients. More than 90% of the patients exhibited complete clearance of stone after single session after 3 months of intervention. There was no ureteral injury and no patient developed stricture. Conclusion: For management of selective sized upper ureteric stone, ESWL is superior to other minimally invasive procedures like ureterorenoscopy + intracorporeal pneumatic lithotripsy (ICPL) considering greater stone clearance, less complications, and non-invasiveness DOI: http://dx.doi.org/10.11593/bje.2013.0103.0020 Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 13-15